Investigation of Heavy Metal Cd, Pb and Cr in Andisols as Affected by the Amelioration of Steel Slag and Rice Husk Bokashi - Rina Devnita; Mahfud Arifin; Apong Sandrawati; Rija Sudirja (Soilrens, 2020)
The application of steel slag and bokashi of husk in Andisols has been acknowledge to decrease P-retention and increase available P. However, steel slag contains heavy metals that may harm soils. The objective of this research was to find out the effect of amelioration steel slag and bokashi of husk in Andisols on the heavy metals contents (Cd, Pb and Cr) in the soil. The treatments were arranged in randomized block designed in factorial pattern with two factors: steel slag and bokashi of husk, each consisted of four level: 0, 2.5, 5.0 and 7.5 % in 10 kg soil weight (w/w), thus the total was 16 combined treatments and repeated three times. The treatments were incubated for four months and then the P-retention, available P, Cd, Pb and Cr contents in the soil were analyzed. The results showed that steel slag and bokashi of husk interacted in decreasing 6.67% of P-retention and increasing 60 ppm of available P. This research also informed that Cd, Pb and Cr contents in the soil after the treatments were still lower than the critical value that were permitted.